Pelatihan Implementasi SAP Berbasis Akrual Pada SDM Pemerintah Provinsi Sumatera Utara (Dinas Lingkungan Hidup Provinsi Sumatera Utara) - Dito Aditia Darma Nst (IAI Darussalam, 2019)
The issuance of accrual-based Government Accounting Standards (SAP)signed by the President requires all government agencies both at the center and in theregions to apply accrual-based SAP as of January 1, 2015. The implementation ofaccrual-based SAP rules cannot yet be fully implemented at the Government levelRegional Government. The local government seems to have difficulties inimplementing the regulation even though the regulation has been socialized since2003, namely at the issuance of Law 17 of 2003 which implies reforming statefinancial governance, one of which is to fully implement SAP accruals. The NorthSumatra Provincial Government which is the object of research conducted by Nasutionand Ramadhan (2018) is one of the regional governments which is deemed necessaryto strengthen HR in terms of accrual-based SAP implementation, namely byimplementing Accrual-Based SAP Implementation Training on the Government ofNorth Sumatra Provincial Government so that the Provincial Government NorthSumatra can better implement the accrual-based SAP maximally. In the case ofconsideration of time constraints and funding, the training was conducted at one ofthe North Sumatra Provincial Government OPDs by taking one of the researchpopulations conducted by Nasution and Ramadhan (2018) randomly. Based on theresults of the determination of the object of training that has been done randomly, theEnvironmental Agency of North Sumatra Province is selected as the OPD in the scopeof the Regional Government of North Sumatra Province which will be the object oftraining for community service. The results of the community service show that thereis an increase in the capacity of the Human Resources Department of the NorthSumatra Province in implementing SAP accrual based maximally which leads to theRegional Government of North Sumatra Province being able to better implementaccrual-based SAP in the future.